Desain Pembelajaran Digital Materi Hikayat Berbasis Literasi Kearifan Lokal di Era Merdeka Belajar - Yoga Rifqi Azizan; Yonita Shelly Anggraeni; Moh. Ahsan Shohifur Rizal; Abdul Kholiq (Hasta Wiyata, 2025)
Distance learning (PJJ) is a learning that is widely applied in the era of the industrial revolution 4.0. PJJ which is based on technology media requires an appropriate and acceptable learning design. This learning also includes the concept of independent learning in it. The concept of Independent Learning contains the concept of freedom and is correlated with the learning process that involves aspects of culture, local wisdom literacy, socio-economics and infrastructure. The learning design used uses the ASSURE model (analyze, state, select media, utilize, requires, evaluate and revise). The purpose of developing a local wisdom literacy-based story learning design is to provide an alternative learning design that is adjusted to the preservation of cultural values in the environment around students digitally. Development begins with a needs test then a design trial. The result is that learning goes well and 100 percent of student scores are above the KKM, which is 75. The scores are divided into knowledge scores and skills scores. The average student knowledge score is 86. The average student skill score based on the results of student short stories is 83. This local wisdom literacy-based learning design has also received a positive response from teachers and students.